Note from Editors - Board, Editorial (Consilience, 2008)
“However unwillingly a person who has a strong opinion may admit the possibility that his opinion may be false, he ought to be moved by the consideration that however true it may be, if it is not fully, frequently, and fearlessly discussed, it will be held as a dead dogma, not a living truth.” – John Stuart Mill Consilience: The Journal of Sustainable Development began as an idea: an idea that a group of ten students genuinely and passionately believed had the potential to make this world a better place. The realization of this idea – the inaugural issue of the journal we present before you – represents the space created to keep John Stuart Mill’s concept of a “living truth” alive. This first issue aims to serve as a stimulus for informed debate on some of the issues most pressing in our world today. Widespread global poverty, hunger, environmental damage, and conflict are only some of the problems facing humanity today. As a bold collective of students intolerant of inertia, we push you to understand the urgency of forging solutions to these problems. Mainly rooted in rigorous research, the seven scholarly articles in this first issue of Consilience all begin to effectively analyze some of these problems from very different angles. Aaron Holdway advocates for policy change in international law while Jisung Park roots his review in economic theory. Pedro Sanchez et al. reveals the importance of science-based interventions for the Millennium Villages while Thomas Lee visually communicates the impact of literacy programs in Afghanistan. The diversity of methodologies employed parallels the variety of academic disciplines in which this inaugural issue is rooted. The problems facing humanity are mired in complexity, and one challenge is often intricately connected to another. For instance, Chikara Onda argues that a steady decrease in freshwater availability correlates to civil war onset in Africa. In this case, environmental science is intimately linked to regional politics. We firmly believe in a more integrated understanding of complex situations gained through an interdisciplinary approach. The concept of consilience, “the joining together of knowledge and information across disciplines to create a unified framework of understanding,” runs through each article. With this in mind, we urge you to be active readers, to not only think deeply about each specific article but also to consider the interaction between the individual pieces. E.O. Wilson claims that “a balanced perspective cannot be acquired by studying disciplines in pieces but through pursuit of the consilience among them.” In his field note, Matthew Bonds observes that the questions that pit economists against ecologists inside the closed walls of academia quickly dissipate when considered in the field. Bonds’ observation is a specific realization of Wilson’s conceptual thread. We urge you to contrast theory against practice, one discipline against another, and your ideas against the authors’ ideas. The Editorial Board ofConsilience has high hopes that this exchange of ideas, sparked by the written and visual media contained in this online space, will contribute to the progress of sustainable development. – The Editorial Board, Spring 2008 con·sil·i·ence (noun): The joining together of knowledge and information across disciplines to create a unified framework of understanding.